2022
DOI: 10.3390/medicina58030402
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Post-Stroke Rehabilitation Is Associated with Lower Risk of Pressure Ulcer Development in Patients with Stroke: Real-World Evidence from a Nationwide, Population-Based Cohort Study

Abstract: Background and Objectives: Multiple factors are associated with pressure ulcer (PU) development, including limited mobility following stroke. We performed a nationwide cohort study to investigate the impact of rehabilitation intensity on the incidence of post-stroke PU. Materials and Methods: Data of patients diagnosed with stroke between 2000 and 2012 were collected from the 2000 Longitudinal Health Insurance Database (Taiwan). Based on the number of rehabilitation sessions attended within 90 days of discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The higher prevalence in the non‐medical service group suggests a need for targeted interventions. This includes enhancing home healthcare services, increasing patient and caregiver education about pressure injury prevention, and improving access to medical resources 27,28 . For patients with access to medical services, the emphasis should be on maintaining the quality of care and ensuring consistent implementation of best practices for pressure injury prevention and management.…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence in the non‐medical service group suggests a need for targeted interventions. This includes enhancing home healthcare services, increasing patient and caregiver education about pressure injury prevention, and improving access to medical resources 27,28 . For patients with access to medical services, the emphasis should be on maintaining the quality of care and ensuring consistent implementation of best practices for pressure injury prevention and management.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research findings concerning the length of stay in ICU and PUs were contradictory [30]. Actually, ICU stay implies limited movements and restricted positions, which are well-known major risk factors for PU onset [30], while stroke patients are at higher risk of immobility-related complications due to cognitive, functional, and sensory deficits [31]. A significant relationship between immobility and PU onset was reported, with a significant association between FIM score at admission and PU onset during hospitalization [31], confirming a protective role of rehabilitation to recover mobility and improve functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Due to long‐term bed rest, limb paralysis and urinary and faecal incontinence, among other factors, most patients with stroke are at increased risk of developing pressure ulcers 34 . Once formed, pressure ulcers not only increase patient suffering, but also prolong hospital stay and impose a heavy financial burden on families 35 . Therefore, effective clinical interventions are needed to prevent and reduce the incidence of pressure ulcers among patients with stroke 36…”
Section: Discussionmentioning
confidence: 99%
“…34 Once formed, pressure ulcers not only increase patient suffering, but also prolong hospital stay and impose heavy financial burden on families. 35 Therefore, effective clinical interventions are needed to prevent and reduce the incidence of pressure ulcers among patients with stroke. 36 The results of this meta-analysis showed that evidence-based nursing interventions, which provide targeted and medically justified nursing measures, can not only reduce the incidence of pressure ulcers in patients with stroke, but also delay the time to occurrence, and improve patient satisfaction and quality of life.…”
Section: Discussionmentioning
confidence: 99%